The Burden of History: Kirkjubæjarklaustur and the Biography of Landscape - Sigrún Hannesdóttir (Religions, 2023)
The importance of landscape has long been recognized within monastic studies, both as an economic and spiritual resource. This paper focuses on the surrounding landscape of a single monastic site, that is Kirkjubæjarklaustur on Síða (south Iceland), one of the two female monasteries established in Medieval Iceland. Through written sources, legends, and placenames, the aim of this paper is to reconstruct the biography of the landscape from before the founding of the monastery to after the Reformation. In particular, the paper considers how the perceived sacredness of the site of Kirkjubæjarklaustur may have been shaped by stories of Christian settlers prior to the monastic foundation and how the monastic memory informed the way in which the landscape was experienced after the Reformation and beyond.